FAKTOR-FAKTOR PENENTU PENINGKATAN KINERJA PEJABAT PEMBUAT KOMITMEN (PPK) PADA SATKER APBN DAN SKPD PROVINSI KALIMANTAN TIMUR - Rizali Rahmawanto; A. Wicaksono; Sugeng P. Budio (Media Teknik Sipil, 2012)
Rizali Rahmawanto1, A. Wicaksono2 & Sugeng P. Budio31,2&3Fakultas Teknik Jurusan Teknik Sipil Universitas Brawijaya MalangAlamat Korespondensi : Jl. MT. Haryono No 167 Malang, IndonesiaABSTRACTThis research aims to find the most dominant factor that determines the Committing Officer(CO) to improve their performance, to determine the performance appraisal field coordinatorCommitting Officer (CO), to know how to improve the performance of the Committing Officer(CO) to achieve targets as per the Contract Performance.Validity test results indicate that all variables are as valid as each item has a value of PearsonCorrelatian amounted to less than 0.05, and the test showed that the value of Cronbach’s Alphagreater than 0.6 so variable and item questionnaire is compliant study. Dominant factor test resultsusing factor analysis showed the dominant factor as a determinant of Committing Officer in improvingthe performance seen from the level of satisfaction is the location factor (55.124%), factor equipment(19.034%), the budget factor (15.718%), personnel factor (6.716% ), partner factor (3.408%).While the dominant factor based on the level of interest is the location factor (69.252%), thebudget factor (20.992%), personnel factor (4.426%), equipment factor (3.523%) and the partnerfactor (1.807%).Keywords: Committing Officer (CO), Performance, Factor Dominant